Critical Perspectives in Canadian Music Education - Beynon, Carol, 1950-; Veblen, Kari K (Book collections on Project MUSE., 2012)
Music education in Canada is a vast enterprise that encompasses teaching and learning in thousands of public and private schools, community groups, and colleges and universities. This book offers a collection of essays that look critically at various global issues in music education from a Canadian perspective.